Altered methylation of specific DNA loci in the liver of Bhmt‐null mice results in repression of Iqgap2 and F2rl2 and is associated with development of preneoplastic foci. Issue 5 (8th February 2017) - Lupu, Daniel S.; Orozco, Luz D.; Wang, Ying; Cullen, John M.; Pellegrini, Matteo; Zeisel, Steven H.
ABSTRACT: Folate B12 –dependent remethylation of homocysteine is important, but less is understood about the importance of the alternative betaine‐dependent methylation pathway—catalyzed by betaine‐homocysteine methyltransferase (BHMT)—for establishing and maintaining adequate DNA methylation across the genome. We studied C57Bl/6J Bhmt (betaine‐homocysteine methyltransferase)‐null mice at age 4, 12, 24, and 52 wk (N = 8) and observed elevation of S‐adenosylhomocysteine concentrations and development of preneoplastic foci in the liver (increased placental glutathione S‐transferase and cytokeratin 8–18 activity; starting at 12 wk). At 4 wk, we identified 63 differentially methylated CpGs (DMCs; false discovery rate < 5%) proximal to 81 genes (across 14 chromosomes), of which 18 were differentially expressed. Of these DMCs, 52% were located in one 15.5‐Mb locus on chromosome 13, which encompassed the Bhmt gene and defined a potentially sensitive region with mostly decreased methylation. Analyzing Hybrid Mouse Diversity Panel data, which consisted of 100 inbred strains of mice, we identified 97 DMCs that were affected by Bhmt genetic variation in the same region, with 7 overlapping those found in Bhmt‐null mice (P < 0.001). At all time points, we found a hypomethylated region mapping to Iqgap2 (IQ motif‐containing GTPase activating protein 2) and F2rl2 (proteinase‐activated receptor‐3), 2 genes that were also silenced and underexpressed, respectively.—Lupu, D. S., Orozco, L. D., Wang, Y., Cullen, J. M., Pellegrini, M., Zeisel, S. H. Altered methylation of specific DNA loci in the liver of Bhmt‐null mice results in repression of Iqgap2 and F2rl2 and is associated with development of preneoplastic foci. FASEB J. 31, 2090–2103 (2017). www.fasebj.org